IMPRESSIONAL TRENDS IN CHINESE OIL PAINTING OF THE FIRST HALF OF THE 20 th CENTURY - Ковальова, М. М.; Чжуанюй, Цю (Art and Design, 2020)
The purpose of the article is to reveal the impressionistic trends in the fine arts of China, determining the originality of the Chinese oil painting development of the 20th century. Methodology. Historical and cultural, comparative, iconographic and iconological methods are used in the study. Results. The study examines the underinvestigated aspects of Chinese painting development in the first half of the 20th century. The retrospective analysis of the pictural art enables tracing the traditions and innovations in the formation of oil painting in China, which prevails at this historical stage of the national art school development. The desire of Chinese artists to preserve the philosophical foundation and theoretical principles of classical ink painting, and at the same time an interest in Impressionism, have become a peculiar feature of Chinese oil painting. The main trends, dominating at the beginning of the century, persist to this day, defining the development of Chinese oil painting in general. It is determined that the decorativeness and thematic repertoire of classical Chinese ink art has been transferred to oil painting, as evidenced by the booming exhibition activities. The study determined that in the first half of the 20th century, the impressionistic trend was spread in the country, which resulted from the study of Japanese and French masters by Chinese masters. The teaching methods and stylistic searches of Chinese artists of the period under study became the foundation of contemporary Chinese art. The latest trends in Chinese oil painting in the first half of the 20th century are: an artistic rethinking, reminiscences of a similar phenomenon in Western European painting of the late XIX – early XX century. The spread of impressionism contributed to the greatest development of still life and landscape genres, and also brought plein air practice to a new level. Many Chinese artists spread impressionistic ideas not only in artistic creation, but also in art history. The scientific novelty lies in the systematization and factual material analysis on this problem, determining the role of the impressionist trend in the Chinese oil painting development. Practical significance. The results of the study can be used in further studies of the history and theory of Oriental art of the 20th century.